Engineering Anisotropic Klein Tunneling in Black Phosphorene through Elemental Substitution. Issue 10 (17th July 2021) - Adhikary, Souren; Mohakud, Sasmita; Dutta, Sudipta
Abstract : Black phosphorene, a puckered honeycomb lattice, exhibits semiconducting behavior with linear and parabolic dispersions along the crystallographic armchair and zigzag directions, respectively, away from Fermi energy. Herein, elemental substitution of P atoms to obtain X P 3 ( X = S i, S ) systems is conducted to shift the Fermi energy in downward or upward directions, respectively, to access those dispersive bands. The first‐principles calculations show a semiconductor‐to‐metallic transition in both S i and S substitutions. In the former case, the presence of hybrid dispersive bands at Fermi energy induces metallicity, whereas S substitution induces excess electrons to shift the Fermi energy upward and align with both linear and parabolic bands in either crystallographic directions. This leads to anisotropic Klein tunneling behavior in S‐substituted black phosphorene, which can be exploited for multiterminal switching devices. Abstract : Sulfur‐substituted black phosphorene system SP3 exhibits linear dispersion, i.e. Klein tunneling, along crystallographic armchair direction, whereas a metallic behavior along crystallographic zigzag direction. This may lead to anisotropic transport behavior with barrierless transport along armchair direction.